Perbedaan Pengaruh Latihan Plyometric Box Jump dan Depth Jump terhadap Peningkatan Power Otot Tungkai Atlet Bolavoli - Zulvia Salsabila Athifah; Muh. Ikhwan Iskandar; Eriek Satya Haprabu (MAN Insan Cendekia Jambi, 2026)
This study compares the effectiveness of Plyometric Box Jump and Depth Jump training in enhancing the leg muscle power of male volleyball athletes aged 13–16 years. Utilizing an experimental method, 30 athletes were equally divided into two groups through the ordinal pairing technique, with the Vertical Jump test serving as the primary measurement instrument.The findings indicate that both training methods yielded a significant impact (p < 0.05). However, the Depth Jump group demonstrated a higher performance increase of 2.4 (4.32%) compared to the Box Jump group at 1.9 (3.43%). Statistically, the Depth Jump proved to be superior, with a net effectiveness margin of 0.89%. In conclusion, the more intensive Stretch-Shortening Cycle (SSC) mechanism in the Depth Jump makes it a more optimal option for enhancing leg muscle power.